A systematic review of the use of Cochrane reviews in clinical guidelines, for lower respiratory disease, in children in the United Kingdom: analysis plan part 2 - Smyth, Alan R. (Unpublished, 2012)
This is part 2 of a document giving the search strategy and statistical analysis plan for the following study.